Multicenter clinical trial on functional evaluation of transoral laser microsurgery for supraglottic laryngeal carcinomas - Ambrosch, Petra; Fazel, Asita; Dietz, Andreas; Fietkau, Rainer; Tostmann, Ralf; Borzikowsky, Christoph (Laryngo-Rhino-Otologie, 2024)
Background Transoral laser microsurgery (TLM) is an accepted and effective treatment strategy for supraglottic carcinomas. Data on oncologic and to a lesser extent functional outcomes have been published by mainly European specialized single institutions. TLM for supraglottic carcinomas has never been tested in a multicenter trial on its applicability as surgical standard at every hospital.Objectives To test the efficacy of TLM supraglottic laryngectomy (TLM-SGL) in terms of swallowing function, oncologic outcome parameters, morbidity, complications of treatment, and quality of life in a multicenter setting.Methods The study is designed as a multicenter (approximately 25 centers), non-randomized, single-arm study with a targeted number of 200 previously untreated patients with squamous cell carcinomas (SCC) of the supraglottic larynx T2/T3 N0–3 M0; UICC stage II–IVa. The surgical treatment consists of TLM-SGL and elective or therapeutic uni- or bilateral selective neck dissection (SND). After pathologic risk stratification adjuvant radio- (RT) or radiochemotherapy (RCT) is indicated. Patients are followed-up for 2 years post surgically. Swallowing function is assessed by fibreoptic endoscopic evaluation of swallowing (FEES). The primary endpoint is aspiration-free swallowing at 12 months as established using FEES and defined as grade < 6 of penetration-aspiration scale (PAS). Secondary endpoints include local control, larynx preservation, overall and disease-free survival, complications and side effects of treatment, prevalence of tracheostomy and percutaneous endoscopic gastrostomy (PEG)-tube-feeding, and dysphagia-specific quality of life (QoL) assessed by the MD Anderson Dysphagia Inventory (MDADI) as well as voice-related QoL assessed by the Voice Handicap Index (VHI).
Keywords: Multicenter clinical trial; health service research; supraglottic laryngeal carcinoma; transoral laser microsurgery; FEES; functional outcomes; oncologic outcomes; larynx preservation